STUDI KOMPARASI METODE FOURIER TRANSFORM INFRARED TERHADAP KOMPENDIAL UNTUK PENETAPAN KADAR ERITROMISIN STEARAT - Arati Mas'ud, Keiko
Analytical method development is performed to obtain quick and accurate results with relatively simple procedures. Development of quantitative analysis using FTIR is being taken into account because it does not require complicated preparation or large quantities of organic solvent. This study aims to design an accurate, fast, and simple alternative method that can used in regular evaluation of erythromycin stearate tablets. Calibration curve is made by plotting area under the derivate curve (AUC) against ?±?ð±??» ?? ?¸ ?¸??®??®±??? ?ð??. Validated method was tested on erythromycin stearate tablets equivalent to 500 mg erythromycin. After verification of compendial method, assay results were statistically compared. There were no difference between standard and tablets???±®?? so that assay can be performed without complicated preparation. Test within range 0.25-1.50% (w/w) standard in KBr produced correlation coefficient (r) ????0.999 and VXO ????2.00% with limit of detection and quantitation 0.05% and 0.18% (w/w) respectively. Recovery rate of accuracy was 92-105% with relative standard deviation of intraday and interday precision ????2.00%. Plot of inhibition diameter against concentration range 30.72-?????ã?? produced r 2 ????0.95 and VXO ????2.00% with LOD and LOQ 1.07 ?¸ ?????ã?mL respectively. Recovery rate within 85-115% meanwhile RSD ????15.00%. Statistically, there was no significant difference in determination result. FTIR quantitative analysis at 1747-1689 cm -1 has met validation acceptance criteria so it can be used as an alternative method to determine level in tablets with advantage of time and cost efficient.